Pengaruh Literasi Ekonomi dan Neuroeconomics terhadap Keputusan Ekonomi PT. Kaltim Prima Coal - Fadillah, Dewi Nur; Riyadi, Riyo; Puri Rahayu, Vitria (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This study aims to determine whether economic literacy affects economic decisions in PT KPC employees, whether neuroeconomics affects economic decisions in PT KPC employees and whether economic literacy and neuroeconomics simultaneously affect the economic decisions of PT KPC employees. This research uses a quantitative approach with the type of explanatory research. The population in this study is employees of PT KPC. The sampling technique in this study used a simple random sampling technique with a total sample of 95 people. The data collection technique carried out is a questionnaire. Test the hypothesis using t test, F test and determination test (R2) while to analyze the data used is multiple linear regression analysis using SPSS program version 26. The results of the study obtained using the t test and F test show that partially economic literacy has a positive and significant effect on economic decisions, neuroeconomics has a positive and significant effect on economic decisions, and simultaneously economic literacy and neuroeconomics have a positive and significant effect on economic decisions. In the coefficient of determination (R2) test, data results of 55.5% were obtained which could be explained by economic literacy and neuroeconomics variables, while the remaining 44.5% were influenced by other variables that were not studied in this study.